1999
DOI: 10.1081/ddc-100102148
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Electrostatic Charge on Inhaled Carrier Lactose Particles by Addition of Fine Particles

Abstract: Triboelectrification affects particle adhesion and agglomeration and hence the formulation, manufacture, and use of dry powder inhaler (DPI) devices. Electrostatic charge measurement of two component mixes of spray-dried or crystalline lactose fine particles (< 10 microns) 0, 5, 10, 15, 20, and 30% w/w with spray-dried or crystalline lactose 63-90 microns, respectively, has been undertaken using a system incorporating pneumatic transport of the mixed powders to a stainless steel cyclone charging device. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…The materials of the mixer vessel (stainless steel) and the device constituents (polypropylene and acetal) influence adhesion as well as the magnitude and polarity of the charges acquired by the powders as a function of the nature of the powder [24]. Furthermore, the addition of a fine-lactose excipient ( 10 μm) to coarse lactose decreases the magnitude of triboelectrification during mixing [25]. The increase in amorphous content and the use of a carrier with a wide PSD affects the polarity and the magnitude of the lactose triboelectric charges [26,27].…”
Section: Electrostatic Chargesmentioning
confidence: 99%
“…The materials of the mixer vessel (stainless steel) and the device constituents (polypropylene and acetal) influence adhesion as well as the magnitude and polarity of the charges acquired by the powders as a function of the nature of the powder [24]. Furthermore, the addition of a fine-lactose excipient ( 10 μm) to coarse lactose decreases the magnitude of triboelectrification during mixing [25]. The increase in amorphous content and the use of a carrier with a wide PSD affects the polarity and the magnitude of the lactose triboelectric charges [26,27].…”
Section: Electrostatic Chargesmentioning
confidence: 99%
“…23 Watano et al, 21 using an electrostatic field strength sensor, reported that lactose (Pharmatose 200M, DMW, International, Veghel, The Netherlands) exhibited a positive charge during a stainless steel fluidized bed test. Bennett et al 24 tested crystalline and spray-dried lactose samples neutralized with a radioactive source in a stainless steel cyclone, obtaining a negative charge in both cases. Murtomaa et al 22 Note from Figure 4 that the absolute value of the volume specific chargeability (mV/0.5 cc) increased as the particle size decreased from the L90 to the M5 grade.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, different mixing sequences were also shown to result in different lung deposition profiles of API (22,23). The addition of fine particles of lactose was also shown to reduce the electrostatic charge of coarse lactose particles (24).…”
Section: Introductionmentioning
confidence: 99%